Effects of Different Infra-Red Irradiations on the Survival of Granary Weevil Sitophilus granarius: Bioefficacy and Sustainability - Keszthelyi, Sándor (Insects, 2021)
SIMPLE SUMMARY: The granary weevil Sitophilus granarius is a cosmopolitan insect that causes substantial damage to many stored products. Control methods based on the use of sustainable, residual insecticide-free methods are gaining importance due to their features such as bioactivity, biodegradability, and ecological safety. However, despite the finding that different irradiation methods have proven efficacious, infrared treatment has not gained widespread application, as different aspects of its application have not yet been explored. In this study, we evaluated the activity-inducing and mortality effect profile of infrared irradiation on S. granarius. The impact of the distance between the radiation emitter and the treated material on the mortality rate was tested in search of optimal results. Adult-perishing and progeny-suppressive effects caused by infrared irradiation in S. granarius were confirmed. Our results point out that the efficacy of treatment depends on the optimal distance between the treated specimen and the emitter. Information on adult-activity triggered by radiation facilitates the application of other control methods and the optimization of their timing. In summary, our findings indicate that the use of infrared irradiation for the post-harvest protection of cereals is feasible, which can contribute to the realization of endeavors aimed at environmentally friendly and residuum-free pest management. ABSTRACT: Sitophilus granarius (L.) is an important pest of stored grain worldwide. In recent years, sustainable methods against it have received attention as grain stock protective means. Our aim was to obtain information about the efficacy of infrared irradiation (IR) against S. granarius in laboratory conditions. The change in adult-activity and median lethal dose (LD(50)) triggered by IR in S. granarius was examined. The insecticidal efficacy in the infested grains was also analyzed at 12, 24, 48, and 72h following exposure to IR (250W), and the progeny-production was assessed 45 days upon the treatment. Based on our findings, total mortality ensued in a grain stock of 50 g at 412 s and a for 100 g grain at 256 s. A significant increase in S. granarius mortality could be observed in the higher grain weight regime, which can be accounted for by the higher heat-absorbance of objects with higher weight. The activity of pests immediately after the beginning of IR increased and subsequently became moderated. The observation of activity-peak brought about by irradiation contribute to the optimization of chemical intervention. This treatment could provide an effective and sustainable technique in integrated pest management.